MYKHAILO DRAHOMANOV’S UKRAINOPHILIAN CONCENTRATION - Піхманець, Р. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article touches on the issue of probable reasons of Mykhailo Drahomanov’s joining the corporation of Ukrainophiles. It is topical since he did not allow himself a thought about Ukraine’s state and political independence, in all ways fought against the tendencies connected with the national idea, always and everywhere stood up for the priorities and values of the Russian empire. The assumptions are grounded as to what led to the named step of understanding Ukrainophilia as one of means of “democratic” russification of “The Southwestern Land”.